Analysis Physical and Mechanical of Particle Boards Raw Materials Nipah Fruit Fiber - Saddikin, M; Nurdin, Hendri; Hasanuddin, Hasanuddin; Primawati, Primawati (Teknomekanik, 2019)
The raw materials of the timber industry, especially furniture, are increasingly difficult to obtain in the quantity and quality needed. The development efforts carried out were utilizing Nipah coir waste as a raw material for making particle boards. Particle boards are panel boards made of wood particles or materials containing lignocellulose. Nipah plants contain 27.3% lignin and 36.5% cellulose which has the potential to be used as raw material for particleboard production. This study aims to reveal the physical and mechanical properties of particleboards made from Nipah fruit fibre with adhesive using tapioca flour. The making of particle board is done with a ratio of 90%: 10%, 80%: 20%, 70%: 30%, 60%: 40%, by giving a pressure of 100 kg / cm2. Particle testing is carried out according to the JIS A 5908 standard (2003). From this study, the optimum results were obtained in variations of 60%:40%. The particle physical properties which have an average density value of 1.15 gr / cm3 and an average moisture content of 5.8%. While the mechanical properties obtained by the value of Modulus of Elasticity an average of 21,188.93 kg / cm2. This shows the particle board variations of 60%: 40% produced to meet the JIS A 5908 (2003) standard. Based on the analysis of the quality variations 60%: 40% of particle boards can be recommended as raw materials for interior furniture.